2015
DOI: 10.18632/oncotarget.5675
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion kurtosis imaging can efficiently assess the glioma grade and cellular proliferation

Abstract: Conventional diffusion imaging techniques are not sufficiently accurate for evaluating glioma grade and cellular proliferation, which are critical for guiding glioma treatment. Diffusion kurtosis imaging (DKI), an advanced non-Gaussian diffusion imaging technique, has shown potential in grading glioma; however, its applications in this tumor have not been fully elucidated. In this study, DKI and diffusion weighted imaging (DWI) were performed on 74 consecutive patients with histopathologically confirmed glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 34 publications
5
79
1
Order By: Relevance
“…who reported no significant differences in minimum, average or maximum ADC (MD) between ACs grades II and III 39. Our data differs from the recent paper by Jiang et al 24,. who found significant differences in mean kurtosis between glioma grades II and III using a semiautomatic process.…”
Section: Discussioncontrasting
confidence: 99%
“…who reported no significant differences in minimum, average or maximum ADC (MD) between ACs grades II and III 39. Our data differs from the recent paper by Jiang et al 24,. who found significant differences in mean kurtosis between glioma grades II and III using a semiautomatic process.…”
Section: Discussioncontrasting
confidence: 99%
“…Most of the samples containing a low FA were identified as proneural samples and showed a significantly better clinical outcome. However, the findings of Jiang et al ., who showed that FA was negatively correlated with KI-6737, a marker of mitosis and hence aggressiveness, seem contradictory. In summary, FA does not seem to be merely attributable to quantitative measures of cellular architecture, but also seems to be related to the expression of specific biological pathways such as the EMT.…”
Section: Discussionmentioning
confidence: 96%
“…showed a high accuracy for the distinction of HGGs from the low-grade gliomas (LGGs) based on mean axial and radial kurtosis values 5,6 . Mean kurtosis has outperformed diagnostically the remainder of the diffusion metrics for grading (WHO grade 2–4) and predicting Ki-67 as a measure of cellularity 7 . Tietze et al .…”
Section: Introductionmentioning
confidence: 99%